Online Learning in the Middle of the Covid-19 Pandemic - Siagian, Ade Onny; Haudi; Ariyanto, Aris; Wijoyo, Hadion (Nusantara Science and Technology Proceedings, 2021)
The purpose of this research on the coronavirus or Covid-19 pandemic breaks the traditional learning process. So, we need a way to solve the challenge. Online learning is a kind of Overcome challenge. This is to understand the implementation of the online learning Management Research Program, School of Management, Bina Sarana Informatika University as an effort to Suppress the spread of COVID 19 in higher education. The research sample is a student of the management research program. Data is collected through interviews through zoom cloud conferences. Data analysis uses the Interactive analysis technology of Miles & Huberman. The results show: (1) Students already have the basic facilities required to participate in online learning; (2) Online learning is flexible in implementation, Able to encourage the emergence of independent learning and motivate students to participate more actively Learning; (3) distance learning encourages the emergence of social distancing behaviors and minimizes. The emergence of the student population so that it may be able to reduce Covid-19’s University environment. Inadequate supervision of students, high-rise buildings, insufficient signal strength, High-cost Internet credits challenge online learning. Improve learning independence, interest and Motivation, the courage to express ideas and question other benefits of online learning.